Exploring Gastronomic Value in Increasing the Competitive Advantage of Traditional Restaurants - Murtini; Hafidza Nash’ul Amrina; Abdul Azis Safii; Latifah Anom (LPPM Institut Teknologi dan Sains Mandala, 2025)
This study aims to identify the factors influencing the formation of gastronomic value and how these factors can create a competitive advantage for traditional restaurants. In the culinary context, gastronomic value encompasses the quality of ingredients, menu innovation, restaurant atmosphere, sensory experience, and sense of place, which serve to differentiate restaurants in an increasingly competitive culinary market. This study uses a descriptive approach and case studies with three traditional restaurants as subjects: Warung Kopi Klotok in Yogyakarta, RM Pawon Sego Lego in Mojokerto, and Warung Rempah in Batu. Data was obtained through semi-structured interviews with owners, managers, and customers, and analysed using QSR-NVivo software. The results indicate that factors such as the use of high-quality local ingredients, an atmosphere that reflects local culture, and sensory experiences play a crucial role in building gastronomic value. Furthermore, restaurants that create a strong sense of place, combining authentic cuisine and a supportive atmosphere, can strengthen their competitiveness in the culinary market.